Development of A Three-Lead Electrocardiograph with Embedded Digital Filter on FPGA for Noise Removel - Pratondo Busono (Jurnal Fisika dan Aplikasinya, 2013)
An ECG is a bioelectrical signal which has important correlation with electrical activity of the heart. The ECG reflects important information regarding the performance of the heart. ECG devices are currently made for different settings applications including patient’s home, ambulance, general practioner offices, emergency wards or public health center. Most of the commercial ECG machine available today is still expensive for public health service in the rural area. Therefore, there is a need to develop a low cost and high performance of threeleadECG machine which can be used for the medical doctor or health practitioner in the rural area. In general, the ECG machine consits of differential amplifier, filters, isolation amplifier,buffer, analog to digital converter, microcontroller with digital signal processor and displaying unit. However, the biggest problem in designing the ECG machine is on the problem with low signal-to-noise ratio. Since, there are many sources of noise such power line interference, DC drift, EMC contraction, electronic noise, and motion artifacts. The goal of the work is to design and develop a low cost ECG machine with digital signal processor for noise removal. For that purpose, a series of digital filters will be embedded in the Xillinx Spartan 6 FPGA as part of digital signal processor. Results show that the prototype of ECG machine can be successfully recording and displaying the ECG signals with the good performance.